Age Stage Two-Sex Life Table Reveals Sublethal Effects of Some Herbal and Chemical Insecticides on Adults of Bemisia tabaci (Hem.: Aleyrodidae) - Fatemeh Jafarbeigi; Mohammad Amin Samih; Mehdi Zarabi; Saeideh Esmaeily (Psyche: A Journal of Entomology)
The sweetpotato whitefly, Bemisia tabaci (Genn.) (Hem.: Aleyrodidae), is an important pest of agriculture in subtropical and tropical areas. In this study, we used the age-stage two-sex life table to evaluate the sublethal effects of the herbal extracts taken from Fumaria parviflora Lam. (Fumariaceae), Teucrium polium L. (Lamiaceae), Calotropis procera (Willd.) R. Br. (Asclepiadaceae), and Thymus vulgaris L. (Lamiaceae) as well as the two commercial synthetic insecticides, pymetrozin and neemarin. The whiteflies were exposed to each insecticide using leaf-dip method. Analysis of life table parameters revealed significant differences (P≤0.05) in the net reproductive rate (R0, NRR), intrinsic rate of increase (rm), and finite rate of increase (λ) among different insecticides. The lowest values of the three population parameters, R0, r, and λ, were observed on whiteflies treated with pymetrozin (2.455, 0.036, and 1.036), T. polium (2.828, 0.044, and 1.045), and neemarin (2.998, 0.046, and 1.047), respectively. Results of this study highlights the satisfactory insecticidal effects of the extract taken from T. polium on B. tabaci, which is comparable to the two commonly used synthetic insecticides.